Modulation of growth, gut microbiota, and health markers in rabbits fed hydroponic barley with or without enzymes - Abdel-Wareth, Ahmed A. A.; Mohamed, Esraa M. H.; Hassan, Hamdy A.; Elamary, Rokia B.; Al-Amgad, Zainab; Lohakare, Jayant (Frontiers in Veterinary Science, 2025)
IntroductionHydroponic barley (HB) has emerged as a sustainable alternative feed ingredient; however, its effects on rabbit physiology and gut health remain underexplored. This study aimed to evaluate the impact of dietary HB, with or without enzyme supplementation, on the growth performance, cecal microbiota, and organ histology of growing rabbits.MethodsSixty male Hy-Plus rabbits were randomly allocated to one of three dietary groups: a control group, a group receiving 25% hydroponic barley (CHB), and a group receiving 25% hydroponic barley supplemented with 0.5 g/kg of AXTRA XB enzymes (CHBE). The feeding trial lasted for 60 days. Growth performance parameters, serum biochemistry, cecal microbiota, and histological features of the liver and intestines were evaluated. Data were analyzed using one-way ANOVA.ResultsRabbits fed the CHB and CHBE diets showed significant improvements in body weight, weight gain, and feed conversion ratio compared to the control group. Both treatment groups exhibited beneficial modulation of cecal microbiota, with increased Lactobacillus spp. and reduced Escherichia coli populations. Serum biochemical profiles were improved, as evidenced by lower levels of aspartate aminotransferase, alanine aminotransferase, urea, creatinine, and cholesterol. Histological examination revealed normal liver and intestinal structures in all treatment groups.DiscussionIncorporating 25% hydroponic barley, with or without enzyme supplementation, improved growth performance, enhanced gut microbiota composition, and supported organ health in growing rabbits. These findings support the potential of hydroponic barley as a functional and sustainable feed ingredient in rabbit production.